A universal direct tensile testing method for measuring the tensile strength of rocks - Yang Wu; Jianfeng Liu; Zhide Wu; Junjie Liu; Yonghui Zhao; Huining Xu; Jinbing Wei; Wen Zhong (International Journal of Mining Science and Technology, 2024)
There is limited applicability to the current method for testing the direct tensile strength of rocks because it places stringent requirements on the testing equipment. This work suggests a universal method based on the “compression-to-tension” idea in response to these difficulties. By applying pressure, this technique makes it possible to test the tensile strength of rocks directly with any conventional compression test machines. Granite was utilized as the test material in order to validate this suggested testing method, and the results showed what follows. Upon determining the true fracture area through digital reconstruction, an average calculated tensile strength of 5.97 MPa with a Cv of 0.04 was obtained. There is a positive correlation between tensile strength and the joint roughness coefficient (JRC) of the failure surface. The aggregation mode of AE events with the loading process conforms to the damage characteristics of rock tensile failure. The direct tensile testing method proposed in this study not only has high universality but also produces test results with outstanding consistency. Additionally, factors influencing the results of the tensile test are pointed out, and recommendations for optimizing the suggested testing method are offered.